2021
DOI: 10.1097/md.0000000000026975
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in patients with chronic myeloid leukemia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(88 reference statements)
2
2
0
Order By: Relevance
“…Consistent with previous reports ( 6 , 16 ), we found that increasing age was significantly associated with PH. In the current study, the age of the patients was 10–15 years younger than those of the studies from western countries ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous reports ( 6 , 16 ), we found that increasing age was significantly associated with PH. In the current study, the age of the patients was 10–15 years younger than those of the studies from western countries ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 93%
“…Nilotinib has been reported to injure vascular endothelial cells by direct pro-atherogenic and anti-angiogenic effects and might be associated with the cumulative effect on the onset of PH ( 20 ). Consistent with previous studies, PH was more likely to occur in elderly patients who received dasatinib therapy ( 6 , 16 ). Understandably, patients with cardiopulmonary comorbidities were prone to develop a high probability of PH when receiving dasatinib therapy.…”
Section: Discussionsupporting
confidence: 90%
“…[8] Pulmonary hypertension and life-threatening cardiac arrhythmias can occur. [9,10] Pulmonary toxicities (e.g., pleural effusion <1%) are rare, as reported in previous clinical trials. [11,12] Previous case reports showed that nilotinib can successfully substitute imatinib in patients with imatinib-induced ILD.…”
Section: Introductionmentioning
confidence: 58%
“…Most commonly reported drug-related adverse events are rash, pruritus and gastrointestinal upset [8] . Pulmonary hypertension and life-threatening cardiac arrhythmias can occur [9,10] . Pulmonary toxicities (e.g., pleural effusion <1%) are rare, as reported in previous clinical trials [11,12] .…”
Section: Introductionmentioning
confidence: 86%